Comparative analysis of traditional and interactive teaching methods - Li, Ting; Koodoevna, Sartbekova Nurzhan; Li, Dehao; Li, Yixiu (Edelweiss Applied Science and Technology, 2025)
In the face of current problems in educational practice, such as insufficient student participation in class, low efficiency in knowledge internalization, and limited development of higher-order thinking skills, this study first constructed a three-dimensional evaluation framework. Subsequently, a structured classroom observation scale was designed, along with a cognitive load scale and a delayed post-test. Finally, a standardized test was combined with an open-ended problem-solving task. The experimental results indicated that the interactive teaching method significantly improved class participation. Specifically, the frequency of questions asked in the interactive class was 2.4 times higher than in the traditional class (p < 0.001). The cognitive load experiment revealed that the average cognitive load during the 12th class was 53.85±3.32. Regarding knowledge transfer ability, scores for basic transfer tasks and advanced transfer tasks in the interactive teaching class were 20.49±3.67 and 20.72±7.19, respectively. These findings demonstrate that the interactive teaching method effectively promotes students' internalization and transfer of knowledge by increasing classroom interaction and reducing cognitive load, particularly in fostering higher-order thinking skills.